Compressing Double [7]Helicene by Successive Charging with Electrons. Issue 37 (15th July 2020) - Zhou, Zheng; Fu, Lin; Hu, Yunbin; Wang, Xiao‐Ye; Wei, Zheng; Narita, Akimutsu; Müllen, Klaus; Petrukhina, Marina A.
Abstract: Chemical reduction of a benzo‐fused double [7]helicene (1 ) with two alkali metals, K and Rb, provided access to three different reduced states of 1 . The doubly‐reduced helicene 1 2− has been characterized by single‐crystal X‐ray diffraction as a solvent‐separated ion triplet with two potassium counterions. The triply‐ and tetra‐reduced helicenes, 1 3− and 1 4−, have been crystallized together in an equimolar ratio and both form the contact‐ion complexes with two Rb + ions each, leaving three remaining Rb + ions wrapped by crown ether and THF molecules. As structural consequence of the stepwise reduction of 1, the central axis of helicene becomes more compressed upon electron addition (1.42 Å in 1 4− vs. 2.09 Å in 1 ). This is accompanied by an extra core twist, as the peripheral dihedral angle increases from 16.5° in 1 to 20.7° in 1 4− . Theoretical calculations provided the pattern of negative charge build‐up and distribution over the contorted helicene framework upon each electron addition, and the results are consistent with the X‐ray crystallographic and NMR spectroscopic data. Abstract : Electron‐transfer driven molecular compression : The first X‐ray crystallographic characterization of the reduced forms of benzo‐fused double[7]helicene (1 ) ranging from 1 2− to 1 4− reveals a gradual core change upon stepwise multiple electron charging.